Salinity, temperature, pH, and fluorescent dissolved organic matter (fDOM) measurements in surface waters within DynaCom experimental islands and saltmarsh enclosed plots at different elevation levels, Spiekeroog, Germany, 2018-08 to 2022-01 - Daniela Pieck; Esther Schilken; Kai Schwalfenberg; Cassidy Slivensky-Graf; Claudia Thölen; Niklas Weyel; Kertu Lõhmus; Helmut Hillebrand; Michael Kleyer; Jochen Wollschläger; Oliver Zielinski; Thomas Henry Badewien (PANGAEA, 2025)
Data were collected between August 2018 and January 2022 as part of the research unit DynaCom (Spatial community ecology in highly dynamic landscapes: From island biogeography to metaecosystems) of the Universities of Oldenburg, Göttingen, and Münster, the iDiv Leipzig and the Nationalpark Niedersächsisches Wattenmeer. Measurements were conducted almost bi-/monthly on experimental islands and salt marsh enclosed plots located in the back barrier tidal flat and salt marsh of the island of Spiekeroog (Germany). Field-based in situ measurements of salinity, temperature, and pH were conducted using portable hand-held instruments in groundwater (filter tubes within experimental plots) and in surface waters from a tidal channel (ITC) adjacent to the experimental islands and a tidal pond (STP) in the pioneer zone of the salt marsh. Measurements were performed and samples were taken during the day between 3 hours before and 3 hours after low tide. From August 2018 to September 2019 a HQ40D digital two-channel multi meter equipped with a pre-calibrated Intellical CDC401 field 4-pole graphite conductivity cell (Hach Lange GmbH, Germany) was used to measure temperature (°C) and salinity (psu). The same device was used for pH measurements with an Intellical PHC101 field low maintenance gel filled pH electrode (Hach Lange GmbH, Germany). The pH electrode was calibrated before each fieldwork using single-use pH buffer solutions (pH 4.01, 7.00, 10.01, Hach Lange GmbH, Germany). Since October 2019, salinity and temperature were measured using a Multi 3510 IDS SET 4 handheld device equipped with a TetraCon® 925/LV 4-Pol-IDS conductivity electrode with graphite cells (WTW, Xylem Analytics Germany GmbH, Germany). Fluorescent dissolved organic matter (FDOM, ppb QSE) was measured using an AquaFluor Modell 80000-010 for UV-420 (Turner Designs Inc., USA), pre-calibrated in the laboratory. For this, water samples were taken from the field to a nearby mobile central field unit and were filtered within 1-2 hours after sampling using 25 mm Nuclepore syringe filters (0.2 μm pore size) directly into sample-pre-rinsed measurement cuvettes. Data quality control (QC) was performed using MATLAB (R2024b). Outlier detection was conducted both visually and statistically using z-score analysis (z > 3) per sampling campaign and plot. Each data point was assigned a Quality Control Flag (QC).